Edukasi Kesehatan - Pentingnya Skrining dan Penerapan Pola Hidup Sehat pada Dewasa Muda di Jakarta Barat - Susy Olivia Lontoh; Muhammad Dzakwan Dwi Putra; Muhammad Naufal Razaan; Anthon Eka Prayoga Khoto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Non-communicable diseases (NCDs) have become the leading cause of death in Indonesia, particularly among young adults, with an increasing incidence rate. Technological advancements, lifestyle changes, and environmental factors have contributed to the rising prevalence of NCDs, especially among the younger generation. In light of this, it is essential to implement prevention through health screening and education on healthy lifestyles, particularly among young adults. This community service activity was conducted on December 20 and 21, 2024, with the aim of raising awareness among young adults in West Jakarta about the importance of adopting a healthy lifestyle through health screenings and the promotion of an active lifestyle, including education on nutrition status, physical activity, quality sleep, and the dangers of smoking, especially the use of e-cigarettes. The results of the activity showed that the majority of participants experienced sleep difficulties, and most did not smoke, although some used e-cigarettes. The results of nutrition status measurements also indicated that most participants fell into the obese category. Participants' physical activity levels were relatively low, with many engaging in less than 30 minutes of exercise per session and struggling to find time for regular physical activity. Education and promotion of healthy lifestyles need to be continuously improved to prevent NCDs among young adults, with a focus on improving eating habits, increasing physical activity, and managing stress.